Comparative Study of Internet of Things (IoT) Platform for Smart Home Lighting Control Using NodeMCU with Thingspeak and Blynk Web Applications - Marina Artiyasa; Ilman Himawan Kusumah; Anang Suryana; Edwinanto; Aryo De Wibowo Muhammad Sidik; Anggy Pradiftha Junfithrana (FIDELITY : Jurnal Teknik Elektro, 2020)
Today's technology has developed rapidly with the Internet of Things (IoT) which is a concept that aims to expand the benefits of continuously connected internet connectivity. Internet of Things (IoT) is a development of network communication of interrelated objects connected through internet communication and can exchange data, turning it into information. Many tools are created to ease human work and even replace human work. Controlling room lights in a house using NodeMCU is one of the Smart Home technologies based on the Internet of Things (IoT). This research can provide information about the differences, advantages and disadvantages of Web, Thingspeak and Blynk applications for Smart Home devices to turn on and off house lights via the internet using laptops and smartphones. NodeMCU is a microcontroller that can be analogous to the Arduino ESP8266 board. NodeMCU includes ESP8266 and is packaged in a compact board with various features such as a microcontroller, WiFi access capabilities, and a USB data cable extension chip, which is used as a data cable and charging cable for Android smartphones. From the analysis results using the three platforms, it is known that Blynk is superior to the other two platforms because the way to create and operate is easier and more efficient